259 Impact of Reducing Dietary Protein with Supplementation of 8 Essential Amino Acids and Functional Roles of Supplemental his or Glu on Growth Performance and Carcass Traits of Finishing Pigs. (21st September 2022) - Duarte, Marcos Elias E; Deng, Zixiao; Baker, Jonathan; Kim, Sung Woo
Abstract: This study evaluated the effects of reducing dietary protein with supplementation of 8 essential amino acids and functional roles of supplemental Glu or His on growth performance and carcass traits of finishing pigs. Pigs (n = 216; 98 ± 3.5 kg BW) were allotted (3 pigs/pen) to 4 treatments in a randomized complete block design (RCBD) with sex and initial BW as blocks. Pigs were fed for 14 d until 120 kg BW. Dietary treatments were CON (11.4% CP with L-Lys, L-Thr, and L-Trp); LCP (8.9% CP with L-Lys, Thr, Trp, Met, Val, Ile, Phe, and His); LCPG (9.1% CP; LCP+Glu to match % Glu in CON); and LCPH (9.2% CP; LCP+2x His requirement). Diets met or exceeded requirements with 2.7 Mcal/kg NE. Growth performance and backfat thickness (BFT) were measured at d 0 and d 14. Blood was collected to analyze BUN. At d 14, pigs with the median BW in each pen were slaughtered. Pigs fed CON had greatest (P < 0.05) BW, ADG, and G:F. Pigs fed LCP had greater (P < 0.05) BW, ADG, and ADFI than LCPG. BFT of pigs fed LCPG and LCPH was less (P < 0.05) than CON. Cold carcass weight in CON was greater (P < 0.05) than LCPG and LCPH, whereas it was greater (P < 0.05) in LCP than in LCPG. Chilling loss in LCP was less (P < 0.05) than LCPG. Drip loss at 48 h in LCPH was less (P < 0.05) than CON and LCPG. BUN in LCPG and LCPH was less (P < 0.05) than CON. In conclusion, reducing dietary protein by 2.5% using 8 supplemental amino acids reduced growth performance without affecting carcass yield. Supplemental His at 2x requirement to low protein diets meeting His requirement enhanced loin quality by reducing drip loss.